Analisis Lingkungan Internal dalam Pencapaian Tujuan dan Penyusunan Strategi Perusahaan - Isza Fina Alfiani; Minkhatul Maula; Reza Latifa Lu’lu’a; Gunawan Aji (Universitas Katolik Widya Karya Malang, 2023)
The research on internal environmental analysis was conducted at PT. Perkebunan Nusantara III (Persero), a public company that focuses on plantation business in Medan, Indonesia. The purpose of this study is to analyze the internal environment in achieving goals and developing company strategies. This research employed a qualitative approach. The conclusion of this study is that the company has not been able to manage its strengths to achieve its goals, but has been successful in managing its human resources, resulting in increased business revenue.